212k views
1 vote
Y=4x+1, 2x+y=37 substitution

User Quasiben
by
5.1k points

1 Answer

4 votes

Answer:

x = 6 and y = 25 → (6, 25)

Explanation:

Substitute y = 4x + 1 to the equation 2x + y = 37:

2x + (4x + 1) = 37

(2x + 4x) + 1 = 37 subtract 1 from both sides

6x = 36 divide both sides by 6

x = 6

Pyt the value of x to the first equation:

y = 4(6) + 1

y = 24 + 1

y = 25

User Frazell Thomas
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.